2021
DOI: 10.1021/acschembio.1c00597
|View full text |Cite
|
Sign up to set email alerts
|

General and Robust Chemoenzymatic Method for Glycan-Mediated Site-Specific Labeling and Conjugation of Antibodies: Facile Synthesis of Homogeneous Antibody–Drug Conjugates

Abstract: Site-specific labeling and conjugation of antibodies are highly desirable for fundamental research and for developing more efficient diagnostic and therapeutic methods. We report here a general and robust chemoenzymatic method that permits a one-pot site-specific functionalization of antibodies. A series of selectively modified disaccharide oxazoline derivatives were designed, synthesized, and evaluated as donor substrates of different endoglycosidases for antibody Fc glycan remodeling. We found that among sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 81 publications
1
45
0
Order By: Relevance
“…Our recent study has shown that wild-type Endo-S2 could accommodate selectively modified disaccharide oxazolines corresponding to the natural disaccharide (Manβ1,4GlcNAc) core for transglycosylation without product hydrolysis. 18 However, whether this enzyme could recognize and transfer unnatural core disaccharide structures to antibodies remains to be tested. We sought to test simpler disaccharide derivatives, such as Glcβ1,4GlcNAc and Galβ1,4GlcNAc (LacNAc) oxazolines, which are much easier to synthesize than the Manβ1,4GlcNAc core.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent study has shown that wild-type Endo-S2 could accommodate selectively modified disaccharide oxazolines corresponding to the natural disaccharide (Manβ1,4GlcNAc) core for transglycosylation without product hydrolysis. 18 However, whether this enzyme could recognize and transfer unnatural core disaccharide structures to antibodies remains to be tested. We sought to test simpler disaccharide derivatives, such as Glcβ1,4GlcNAc and Galβ1,4GlcNAc (LacNAc) oxazolines, which are much easier to synthesize than the Manβ1,4GlcNAc core.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…18 The resulting azide-tagged antibodies can be efficiently converted to homogeneous ADCs with different antibody/ drug ratios by subsequent click reactions. 18 To further examine the scope of this method, we report herein the synthesis and evaluation of selectively modified new disaccharide oxazolines, including the Glc-β1,4-GlcNAc and Gal-β1,4-GlcNAc (Lac-NAc) disaccharides, as substrates for enzymatic Fc-glycan remodeling of antibodies. We found that wild-type Endo-S2 had a remarkable flexibility to accommodate the "unnatural core disaccharides" for transglycosylation to provide azidefunctionalized antibodies (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The use of the selectively azide‐tagged bi‐antennary N‐glycan for Fc glycan remodeling and subsequent conjugation has several advantages, including the site‐specific conjugation and the preservation of the natural Fc N‐glycan core after remodeling, which could be important for maintaining antibody stability and favorable pharmacokinetic property. Our previous studies have demonstrated that glycosynthase EndoS2‐D184 M possesses quite relaxed substrate specificity in transferring different natural and selectively modified glycan oxazolines, [10,14] Recently, we have shown that both the wild type and the EndoS2‐D184 M mutant of Endo‐S2 can efficiently transfer selectively azide‐functionalized Manβ1,4‐GlcNAc oxazoline to the deglycosylated antibody for constructing homogeneous antibody‐drug conjugates [14a] . This method could provide an alternative approach for making the antibody‐rhamnose or αGal cluster conjugates.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, IgG-specific ENGases have been shown to ameliorate autoimmune disease in diverse animal models [10][11][12][13] . In addition, EndoS and EndoS2 are powerful tools for the chemoenzymatic synthesis of antibodies with homogenous glycoforms [14][15][16][17] and drug conjugates 18,19 . The Fc region N-glycans of IgG antibodies in serum are composed of more than 33 distinct glycoforms 20 and their unique chemical structures modulate the effector functions by altering Fc binding to FcgRs, as well as the stability and half-life of the antibody 21 .…”
Section: Introductionmentioning
confidence: 99%